INCREASING TEACHER PERFORMANCE IN THE DEVELOPMENT OF TEACHING MATERIALS THROUGH ACADEMIC SUPERVISION AS AN EFFORT TO INCREASE QUALITY ACHIEVEMENTS IN SDN 23 BALAI NARAS ACADEMIC YEAR 2020/2021 - Novi Yarmaneti (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
Problem important which often faced teacher in activity learning is choose or determine appropriate learning materials or teaching materials in order to help students achieve competence. Thing This is due to the fact that in the curriculum or syllabus, teaching materials are only written down broadly in the form of "subject matter". It is the teacher's job to describe the main material so that it becomes a complete teaching material. In addition, how to use teaching materials is also a problem. The intended use is how to teach it in terms of the teacher, and how to learn it from the student's point of view. The purpose of school action research ( PTS) is to find out the extent to which the principal's guidance improves teacher performance in selecting teaching materials. In this school action research (PTS), it is carried out in 3 cycles, from results action which conducted proven could increase performance teacher with reach standard ideal.From 64.47% on cycle I, could increase Becomes 74.59% on cycle II, and cycle to III 83.29%. Results study action this show that construction through supervision academic can improve teacher performance in choosing teaching materials at SDN 23 Balai Naras.